1997
DOI: 10.1001/archneur.1997.00550140045011
|View full text |Cite
|
Sign up to set email alerts
|

Language-Associated Cortical Regions Are Proportionally Larger in the Female Brain

Abstract: Our results suggest that females have proportionally larger Wernicke and Broca language-associated regions compared with males. These anatomical differences may correlate with superior language skills previously demonstrated in females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
116
1
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(135 citation statements)
references
References 33 publications
13
116
1
2
Order By: Relevance
“…One of these regions is the left PFC, including the left IFG (BA 45͞47) and left MFG (BA 46), suggesting greater emphasis on language and executive processing in women. Females have been credited with dominance in language-based approaches to processing stimuli (29,30), a finding consistent with reportedly larger volumes of Broca's area (42) and the DLPFC (43) in women. Prior studies also have revealed greater left IFG activity in women during emotionally incongruous semantic processing, a cognitive paradigm analogous to reconciling the juxtaposed and emotioneliciting components of a humorous stimulus (44).…”
Section: Discussionsupporting
confidence: 61%
“…One of these regions is the left PFC, including the left IFG (BA 45͞47) and left MFG (BA 46), suggesting greater emphasis on language and executive processing in women. Females have been credited with dominance in language-based approaches to processing stimuli (29,30), a finding consistent with reportedly larger volumes of Broca's area (42) and the DLPFC (43) in women. Prior studies also have revealed greater left IFG activity in women during emotionally incongruous semantic processing, a cognitive paradigm analogous to reconciling the juxtaposed and emotioneliciting components of a humorous stimulus (44).…”
Section: Discussionsupporting
confidence: 61%
“…More specifically female brains have been shown to have larger language associated areas than males and increased verbal processing capacity in the right hemisphere compared to males (Annett 1991;Harasty, Double, Halliday, Kril & McRitchie, 1997). Studies have consistently reported that the degree of lateralisation is less in females than in males (Kansaku & Kitazawa, 2001;Levy & Gur, 1980;McGlone, 1980; Shaywitz, et al, 1995).…”
Section: Neuropsychological Evidence For Gender Differencesmentioning
confidence: 99%
“…Because higher brain functions are related to the activity of the neocortex, many studies aimed at identifying possible structural correlations for cognitive gender differences have focused on the cerebral cortex, using a variety of anatomical and brain imaging techniques. At the macroscopic level, sexual dimorphism has been reported in the cortical volume of the Wernicke and Broca areas (6), as well as in the frontal and medial paralimbic cortices (7)(8)(9)(10), and in the thickness and density of the gray matter in the parietal lobes (for a review see ref. 10).…”
mentioning
confidence: 99%